PENGARUH ANGGARAN BERBASIS KINERJA TERHADAP AKUNTABILITAS KINERJA INSTANSI PEMERINTAH - Darnawati Darnawati; Herman Haluti; Bala Bakri; Reyther Biki (Universitas Ichsan Sidenreng Rappang, 2025)
This study aims to find and analyze the effect of performance-based budgeting on the performance accountability of government agencies at the Secretariat of the Regional People's Representative Council of Gorontalo City. Quantitative method is applied in this study using a survey data collection by sampling a single population. It employs a questionnaire as a data collection tool. Data analysis uses path analysis to test the hypotheses. The results of the study indicate that the first hypothesis, the performance-based budgeting, consisting of the sub variables of performance measurement (X1), rewards and punishments (X2), performance contracts (X3), external and internal control (X4), and management accountability (X5), simultaneously has a positive and significant effect on performance accountability at the Secretariat of the Regional People's Representative Council of Gorontalo City, namely 0.935 (93.50%), with the remaining 0.065 (6.50%) influenced by other variables unexamined, such as budget participation. The second, third, fourth, fifth, and sixth hypotheses, namely the sub variables performance measurement (X1), rewards and punishments (X2), performance contracts (X3), external and internal control (X4), and management accountability (X5), also have a positive and significant effect on performance accountability, amounting to 4.20%, 7.40%, 3.50%, 2.70%, and 16.70%, respectively.